Current concepts in imaging for local staging of advanced rectal cancer. Issue 8 (August 2019) - Brown, P.J.; Hyland, R.; Quyn, A.J.; West, N.P.; Sebag-Montefiore, D.; Jayne, D.; Sagar, P.; Tolan, D.J.
Abstract : Imaging of rectal cancer has an increasingly pivotal role in the diagnosis, staging, and treatment stratification of patients with the disease. This is particularly true for advanced rectal cancers where magnetic resonance imaging (MRI) findings provide essential information that can change treatment. In this review we describe the rationale for the current imaging standards in advanced rectal cancer for both morphological and functional imaging on the baseline staging and reassessment studies. In addition the clinical implications and future methods by which radiologists may improve these are outlined relative to TNM8.